1990
DOI: 10.1007/bf00154366
|View full text |Cite
|
Sign up to set email alerts
|

p-mode absorption in the giant active region of 10 March, 1989

Abstract: A time series of velocity oscillations is observed in the vicinity of NOAA region 5395 with the Kitt Peak vacuum telescope for 6.8 hours on 1989 March 10 as part of a program to study the interaction of solar p-mode oscillations with solar active regions. The data is transformed in a cylindrical coordinate system centered on the visible sunspot, then Hankel-and Fourier-transformed to produce the power spectra of inand outgoing acoustic waves. It is observed that a maximum of nearly 70% of the power of incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 10 publications
(3 reference statements)
2
15
0
1
Order By: Relevance
“…This seismic response was stronger than would be expected, both from the current model of flares as giant electromagnetic explosions in the upper chromosphere and corona, and from previous attempts to detect the seismic response in ground-based data 1,2 . The solar surface is covered by lowfrequency (3 millihertz) sound waves that are stochastically excited in millions of small convective elements.…”
mentioning
confidence: 60%
“…This seismic response was stronger than would be expected, both from the current model of flares as giant electromagnetic explosions in the upper chromosphere and corona, and from previous attempts to detect the seismic response in ground-based data 1,2 . The solar surface is covered by lowfrequency (3 millihertz) sound waves that are stochastically excited in millions of small convective elements.…”
mentioning
confidence: 60%
“…In either manifestation, they are again characterized by a broad distribution of oscillation frequencies, but a peak power shifted to between 4 and 5 mHz. (Abdelatif et al 1986;Alamanni et al 1990;Braun & Duvall Jr 1990;Brown et al 1992;Penn & LaBonte 1993;Toner & LaBonte 1993;Balthasar et al 1996Balthasar et al , 1998Lindsey & Braun 1998a,b;Braun & Lindsey 1999;Kumar et al 2000;Thomas & Stanchfield 2000;Muglach 2003;Finsterle et al 2004). The time-series has been filtered to emphasize the five-minute oscillations (a) and three-minute (c) separately.…”
Section: The Observationsmentioning
confidence: 99%
“…This implies that mode energy slowly decreases with B of flaring ARs. This is perplexing as several studies have reported strong p-mode power absorption by ARs' magnetic fields (Braun et al 1987;Braun & Duvall 1990;Rajaguru et al 2001;Mathew 2008). Therefore, mode energy is expected to decrease faster with increasing B rather than with the rate as inferred by the small slope for energy difference for the flaring ARs in Figure 9.…”
Section: Mode Energymentioning
confidence: 95%
“…ically quiet regions. Significant reduction of p-mode energy in ARs has been attributed to absorption by sunspots (Braun et al 1987;Braun & Duvall 1990;Bogdan et al 1993;Zhang 1997;Hindman & Brown 1998;Haber et al 1999;Mathew 2008;Gosain et al 2011). Their studies showed that mode power absorption changes with harmonic degree and radial order.…”
Section: Introductionmentioning
confidence: 99%